Farväl till en stor grupp adverb - En breddad prepositionskategori i ordboksartiklar? - Martola, Nina (Nordiske Studier i Leksikografi, 2012)
In the comprehensive Norwegian grammar, Norsk referansegrammatikk (NRG), a new categorization of prepositions and adverbs is introduced. Several types of words, which we have been used to regarding as adverbs, are classified in the NRG as prepositions, more precisely as intransitive prepositions. In this article I discuss the implications such a recategorization would have for Swedish lexicography, both monolingual and bilingual. My conclusion is that it does not necessarily lead to increased transparency of dictionary items for the categories, and that it is wiser to wait with reforms of this kind until a new categorization is well established within general grammar.